DDA 농업협상 쟁점과 대응방향 - 임송수 (한국농촌경제연구원, 2008)
This research addresses the issues of market access, domestic support and export competition within the Falconer's revised draft text for agriculture and analyzes their potential economic impacts on the agricultural sectors in Korea. The proposed tariff cut formula coupled with the assumed treatment of sensitive and special products would bring about a reduction in bound tariff up to 44 percent. A static analysis shows losses in agricultural production in monetary terms because of increased imports. Ginseng production would fall by 18 percent followed by garlic(16 percent) and chickens(14 percent). The provision for special and differential treatment contributes to relatively low production contractions for sensitive products such as meats, pepper, barley and Korean citrus. Among the proposed guidelines for domestic support, product-specific AMS ceilings and Blue Box limits are of great concern, because they might influence on the direction of rice support policies in the future. To ensure sufficient room for a switch from AMS to Blue Box, it is recommended to use the base period 1995~2000 in AMS calculations and take advantage of the transfer mechanism between the two. When preparing its Country Schedule the government must estimate quota equivalents of tariff reduction and compare them with quota concession for sensitive products. It is because the treatment of sensitive products may not always far superior to normal cuts. It is pivotal for the country to maintain developing country's status with which Korea may be able to take soft landing or achieve gradual policy reforms. In this regard, an important question is if the country is ready and in a position to accept greater responsibilities in policy reforms.